2007
DOI: 10.1198/000313007x245122
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for Working–Correlation–Structure Selection in GEE

Abstract: Efficiency of analysis using generalized estimation equations is enhanced when intracluster correlation structure is accurately modeled. We compare two existing criteria (a quasi-likelihood information criterion, and the Rotnitzky-Jewell criterion) to identify the true correlation structure via simulations with Gaussian or binomial response, covariates varying at cluster or observation level, and exchangeable or AR(1) intracluster correlation structure. Rotnitzky and Jewell's approach performs better when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 6 publications
4
48
0
1
Order By: Relevance
“…The lower the QIC, the better fit the correlation structure reveals (Hin, Carey, & Wang, 2007;Pan, 2001). The QIC for the current analyses indicated that the AR1 (auto-regressive) structure is to be preferred (available upon request).…”
Section: Methodsmentioning
confidence: 82%
“…The lower the QIC, the better fit the correlation structure reveals (Hin, Carey, & Wang, 2007;Pan, 2001). The QIC for the current analyses indicated that the AR1 (auto-regressive) structure is to be preferred (available upon request).…”
Section: Methodsmentioning
confidence: 82%
“…In the past, different proposals were done to select the best correlation structure, including the Rotnitzky-Jewell's criterion (RJ(R)) [23] and the quasi-likelihood under the independence criterion (QIC(R)) [21]. Hin et al [11] conclude that none of these two methods can be regarded as a dominant criterion for working correlation selection in GEE. A data-driven selection procedure to identify an appropriate correlation structure seems to be still an open problem.…”
Section: Selection Of Mean Structure and Covariance Structurementioning
confidence: 98%
“…Hin et al (2007) described the Rotnitzky-Jewell criterion (rj) to select the working correlation structure as…”
Section: Rotnitzky-jewell's Criterionmentioning
confidence: 99%